1999
DOI: 10.1111/j.1745-6584.1999.tb01124.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Geochemical and Isotopic Approaches for Assessing Ground Water NO3 Elimination in a Riparian Zone

Abstract: During the last 40 years, nitrate (NO3−) has become one of the most common ground water contaminants. Stream riparian zones are considered important ecological ecotones that decrease the NO3− load of ground water discharging into streams. This study uses NO3−/Cl− ratios, natural abundances of15N and18O in NO3−, and an in situ15NO3− tracer experiment to evaluate NO3− reducing processes occurring in ground water within a narrow grassed buffer strip bordering a stream in an agricultural watershed. The NO3−/Cl− ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
180
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(204 citation statements)
references
References 33 publications
21
180
1
1
Order By: Relevance
“…Hydraulic gradients are low at the site compared to what has been observed in other riparian wetlands in the region (e.g., Macrae, 2003;Mengis et al, 1999;Stainton, 2000). Hydraulic conductivities, which are generally characteristic of a sand-silt substrate (Freeze and Cherry, 1979) are comparable in magnitude to what has been observed elsewhere in the region (e.g., Macrae, 2003;Mengis et al, 1999;Stainton, 2000;Warren et al, 2001), but more variable than what has typically been observed within individual studies, demonstrating the fact that a large degree of heterogeneity exists at this site. Surface and shallow soils (50 cm) are more conductive than deeper soils, facilitating a greater groundwater flux in this layer.…”
Section: Riparian Zone Hydrologymentioning
confidence: 84%
“…Hydraulic gradients are low at the site compared to what has been observed in other riparian wetlands in the region (e.g., Macrae, 2003;Mengis et al, 1999;Stainton, 2000). Hydraulic conductivities, which are generally characteristic of a sand-silt substrate (Freeze and Cherry, 1979) are comparable in magnitude to what has been observed elsewhere in the region (e.g., Macrae, 2003;Mengis et al, 1999;Stainton, 2000;Warren et al, 2001), but more variable than what has typically been observed within individual studies, demonstrating the fact that a large degree of heterogeneity exists at this site. Surface and shallow soils (50 cm) are more conductive than deeper soils, facilitating a greater groundwater flux in this layer.…”
Section: Riparian Zone Hydrologymentioning
confidence: 84%
“…Additionally, process understanding can be attained by e.g., determination of Cl/NO 3 ratios differences in natural abundance of 15 N (denoted as d 15 N) of NO 3 -N in groundwater. An increase in the Cl/NO 3 ratio indicates that nitrate removal processes occur, e.g., denitrification (Altman and Parizek 1995;Mengis et al 1999). Crop uptake also results in increasing Cl/NO 3 ratios because relative NO 3 uptake rates exceed Cl uptake rates (Marschner 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency was mainly related to the width of the buffer strip. Typically, these studies were conducted on sloping fields with shallow groundwater levels (< 3 m) and/or with a shallow, nearly impermeable soil layer (e.g., Hefting and De Klein 1998;De Klein and Hefting 1998;Dhondt et al 2002;Lowrance et al 2000;Haycock and Burt 1993;Haycock and Pinay 1993;Novak et al 2002;Mengis et al 1999). Such conditions (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, "extra" reduction capacity must be present in the sediments for appreciable amounts of nitrate reduction to occur. Organic carbon is the most common electron donor, and its role in the reduction of nitrate has been studied in both field [e.g., Trudell The ability of stream riparian zones to remove nitrate has been promoted as a way to reduce the effects of pollution from nonpoint sources [Osbourne and Kovacic, 1993;Mengis et al, 1999]. Stream riparian zones are defined as those areas which have direct interaction between terrestrial and aquatic ecosystems with boundaries of the riparian zone extending outward to the extent of flooding [Gregory et al, 1991].…”
Section: Introductionmentioning
confidence: 99%